2023
DOI: 10.1177/20531680231200692
|View full text |Cite
|
Sign up to set email alerts
|

How politicians learn about public opinion

Stefaan Walgrave,
Karolin Soontjens

Abstract: Politicians learning about public opinion and responding to their resulting perceptions is one key way via which responsive policy-making comes about. Despite the strong normative importance of politicians’ understanding of public opinion, empirical evidence on how politicians learn about these opinions in the first place is scant. Drawing on survey data collected from almost 900 incumbent politicians in five countries, this study presents unique descriptive evidence on which public opinion sources politicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Direct contact between constituents and legislators can have substantial effects on their respective perceptions of constituency public opinion ( 68 ) and influence support for bills ( 69 ). Thus, such mobilization during times that are often seen as policy windows for gun regulation might help explain why gun regulation remains elusive despite widespread public support.…”
Section: Discussionmentioning
confidence: 99%
“…Direct contact between constituents and legislators can have substantial effects on their respective perceptions of constituency public opinion ( 68 ) and influence support for bills ( 69 ). Thus, such mobilization during times that are often seen as policy windows for gun regulation might help explain why gun regulation remains elusive despite widespread public support.…”
Section: Discussionmentioning
confidence: 99%
“…sizes in the study of elite responsiveness to public opinion on foreign policy, we suggest that future research should primarily aim to systematically explore the context dependence of the responsiveness mechanism. rely on many other channels -including direct contact with citizens, news media, and interest groups -to inform themselves about public opinion, and that opinion polling may in fact not be an especially useful or important source of public opinion information to them (Walgrave and Soontjens 2023). Related research has shown that cues from social peers are relevant information in determining ordinary citizens' support for foreign policy (Kertzer and Zeitzoff 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The literature highlights the vital need for policymakers to assess and respond to public perception, given its significant impact on governance and diplomatic relations. Walgrave and Soontjens (2023) highlight the significant influence of public opinion on policy decisions, while Walgrave, Soontjens, and Sevenans (2022) elaborate on its pervasive impact on agendas and communication strategies. Davison's contribution to the Encyclopedia Britannica (2024) extends this discussion to emphasize the diplomatic ramifications of a nation's global public opinion standing.…”
Section: Understanding Public Opinion and Policy Decisionsmentioning
confidence: 99%